Marriage and divorce in islam - Shaukat Ali, Zeenat (Bombay, 1987)
It is true that words used in verbatum are primarily and ordinarily the most reliable source of interpreting the meaning of any writing. It should, however, be borne in mind that laws relating to all subjects have a purpose or object to accomplish, whose sympathetic discovery is the surest guide to their meaning. MARRIAGE AND DIVORCE IN ISLAM - An Appraisal is an analysis of the revival of interest in Islamic jurisprudence relating to the institution of marriage and divorce, particularly in regard to the position of women. Most muslim countries in the world today have adopted the dynamic principle of ljtehad forming independent judgements on legal questions in relating to the aforesaid topics.
Keywords: Islamic law